2008
DOI: 10.1371/journal.pbio.0060258
|View full text |Cite
|
Sign up to set email alerts
|

Profound Context-Dependent Plasticity of Mitral Cell Responses in Olfactory Bulb

Abstract: On the basis of its primary circuit it has been postulated that the olfactory bulb (OB) is analogous to the retina in mammals. In retina, repeated exposure to the same visual stimulus results in a neural representation that remains relatively stable over time, even as the meaning of that stimulus to the animal changes. Stability of stimulus representation at early stages of processing allows for unbiased interpretation of incoming stimuli by higher order cortical centers. The alternative is that early stimulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
141
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(152 citation statements)
references
References 77 publications
10
141
1
Order By: Relevance
“…It has been reported that in the aspects of LFP signals and spiking rates, task-related learning processes can modify the neural representation (40,41). However, the objective modulation does not contradict the results in this study, because the task-related modified representations are also stable after the animals learned the task (40).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…It has been reported that in the aspects of LFP signals and spiking rates, task-related learning processes can modify the neural representation (40,41). However, the objective modulation does not contradict the results in this study, because the task-related modified representations are also stable after the animals learned the task (40).…”
Section: Discussioncontrasting
confidence: 75%
“…However, the objective modulation does not contradict the results in this study, because the task-related modified representations are also stable after the animals learned the task (40). Therefore, the modification just redefines the stimulus to generate a new representation and perception accordingly, conferring the system with higher efficiency for complex olfactory functions.…”
Section: Discussionmentioning
confidence: 46%
“…Olfactory learning also induces changes in encoding of the learned odor in the olfactory bulb (OB) (Freeman and Schneider 1982;Wilson and Sullivan 1994;Mandairon et al 2006;Doucette and Restrepo 2008) and the orbitofrontal cortex (OFC; Schoenbaum et al 1998Schoenbaum et al , 1999Schoenbaum et al , 2003. In particular, we have reported (Cohen et al 2008) an enhancement of reciprocal connectivity between the PC and its ascending input from the OB and descending input from the OFC 3 days after learning.…”
Section: Introductionmentioning
confidence: 92%
“…Indeed, when animals perform correctly a discrimination task, gamma oscillations are enhanced (Beshel et al, 2007), whereas mitral cell responses are hardly detectable by measuring single-cell firing rate (Kay and Laurent, 1999;Doucette and Restrepo, 2008). Although the dendrodendritic synapse is essential for gamma oscillation generation, the physiological mechanisms underlying these oscillations are not well understood.…”
Section: Delayed and Long-lasting Effects On Gamma Oscillations And Dmentioning
confidence: 99%